1999
DOI: 10.1038/sj.ejhg.5200311
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 477 psoriatics revealed an increased frequency of aberrations involving chromosome region 11q

Abstract: Psoriasis is an inflammatory skin disorder affecting approximately 3% of the population. Genetic studies published so far have shown a complex genetic inheritance with heterogeneity and a putative major susceptibility locus in the HLA region on chromosome 6. We have collected a large amount of material consisting mostly of small nuclear families in order to perform a genome-wide scan for psoriasis-associated genes. In order to focus the scan properly on possible candidate regions, we performed a cytogenetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The two findings on chromosome 3, on markers D3S1768 and D3S1551 respectively, were detected when the analysis was made on the stratified material. In a recent study of ours, 477 individuals from different families and affected with psoriasis were cytogenetically analyzed for the presence of chromosomal aberrations (Enerbäck et al 1998). The chromosomal region around D3S1551 has been further analyzed in an extended family set by linkage and association studies.…”
Section: Novel Candidate Regionsmentioning
confidence: 99%
“…The two findings on chromosome 3, on markers D3S1768 and D3S1551 respectively, were detected when the analysis was made on the stratified material. In a recent study of ours, 477 individuals from different families and affected with psoriasis were cytogenetically analyzed for the presence of chromosomal aberrations (Enerbäck et al 1998). The chromosomal region around D3S1551 has been further analyzed in an extended family set by linkage and association studies.…”
Section: Novel Candidate Regionsmentioning
confidence: 99%
“…Accelerated telomere shortening could be one such factor, and this possibility has not so far been explored in IBD PBLs. Telomere shortening is accelerated in PBLs in inflammatory diseases such as rheumatoid arthritis, 23, 24 lupus erythematosus, 25 psoriasis 26, 27 and atopic dermatitis, 26 some of which are also associated with chromosome instability 28–31 …”
Section: Introductionmentioning
confidence: 99%
“…A study that included cytogenetic analysis of 477 psoriatic patients revealed an increased frequency of aberrations involving chromosome region 11q. Some of these were balanced translocations that had a breakpoint in the same q12–13 locus 6 …”
Section: Introductionmentioning
confidence: 99%